Using physical and electrical methods in conductive meat frying - Черевко, Олександр Іванович; Скрипник, Вячеслав Олександрович; Молчанова, Наталія Юріївна (Technology audit and production reserves, 2015)
The process of conductive meat frying is inefficient in terms of energy costs and heavy losses of raw materials. Our studies of mass conductivity in meat under the influence of heat flow from electric heaters through a flat metal wall, potential difference and pressure allowed to reveal patterns of occurrence of flow of matter on the basis of which reasonable factors of conductive frying were substantiated and their impact on the effectiveness of the process were developed taking into account technological requirements. The analytical method established the theoretical duration of processes of double-sided frying of meat in the conditions of compression and double-sided process under the influence of a thermal stream from heaters and a difference of potentials which is confirmed by experimental data. Using physical and electrical controls over meat during conductive frying allow significantly to intensify the process, to increase its energy efficiency and output of the finished product without formation of heterocyclic amines in a crust of products. Technical solutions as to implementation of the process of conductive frying under these methods are proposed, specifications of developed devices are given.